Post-trial access to and use of pre-exposure prophylaxis in Durban, South Africa - Ivana Beesham; Cecilia Milford; Jenni Smit; Dvora L. Joseph Davey; Jared M. Baeten; Renee Heffron; Mags Beksinska; Leila E. Mansoor (BMC, 2023)
Abstract Background HIV endpoint-driven clinical trials increasingly provide oral pre-exposure prophylaxis (PrEP) as standard of prevention during the trial, however, among participants desiring to continue using PrEP at trial exit, little is known about post-trial PrEP access and continued use. Methods We conducted one-time, semi-structured, face-to-face, in-depth interviews with 13 women from Durban, South Africa, from November to December 2021. We interviewed women who initiated oral PrEP as part of the HIV prevention package during the Evidence for Contraceptive Options and HIV Outcomes (ECHO) Trial, elected to continue using PrEP at study exit, and were given a 3-month PrEP supply and referred to facilities for PrEP refills at the final trial visit. The interview guide probed for barriers and enablers to post-trial PrEP access, and current and future PrEP use. Interviews were audio-recorded and transcribed. Thematic analysis was facilitated using NVivo. Results Of the 13 women, six accessed oral PrEP post-trial exit, but five later discontinued. The remaining seven women did not access PrEP. Barriers to post-trial PrEP access and continued use included PrEP facilities having long queues, inconvenient operating hours, and being located far from women's homes. Some women were unable to afford transport costs to collect PrEP. Two women reported visiting their local clinics and requesting PrEP but were informed that PrEP was unavailable at the clinic. Only one woman was still using PrEP at the time of the interview. She reported that the PrEP facility was located close to her home, staff were friendly, and PrEP education and counselling were provided. Most women not on PrEP reported wanting to use it again, particularly if barriers to access could be alleviated and PrEP was easily available at facilities. Conclusions We identified several barriers to post-trial PrEP access. Strategies to enhance PrEP access such as a reduction in waiting queues, convenient facility operating hours, and making PrEP more widely available and accessible are needed. It is also worth noting that oral PrEP access has expanded in South Africa from 2018 till now and this could improve access to PrEP for participants exiting trials who desire to continue PrEP.